PUTTING THE CART BEFORE THE HORSE: HOW MONGOLIANS BEGAN TO WRITE THEIR NAMES BACK TO FRONT: Alan Sanders - Alan Sanders (Acta Mongolica, 2012)
During the communist period in Mongolia the word ovog (овог clan name) was used to mean patronymic (father’s name). In 1991 President Punsalmaagiin Ochirbal called on citizens to restore the national tradition of "knowing their clan names and heredity; and keeping a family tree,” which had been banned since the 1920s. His words were reinforced by the National Security Concept (June 1994). which said: ’’Mongolia shall revive on public initiative the tradition of keeping track of the family genealogy to 7-9 generations of ancestors." This was followed in January 1997 by a government decree on keeping a family tree (Ургийн бичиг хөтлөх журам), saying that three names, the clan name (ovog), father’s name or patronymic (эцгийн нэр) and personal name (өөрийн нэр). in that order, were to be used in identity papers (иргэний паспорт), foreign travel passports (гадаад паспорт), birth and marriage certificates, national census returns, and other official documents.